Reply to "Comment on: Depositional palaeoenvironments in a tide-influenced delta plain with amphibian and Cycadophyta remains - the Triassic Zarzaitine Formation (Algerian eastern Sahara) by S. Mazrou, Y. Lasnami, J. Amer, A. Boutaleb: Geologos 30, 3" - Mazrou, S.; Boutaleb, A. (Geologos, 2025)
In a recent paper entitled, “Depositional palaeoenvironments in a tide-influenced delta plain with amphibian and Cycadophyta remains – the Triassic Zarzaitine Formation (Algerian eastern Sahara)” (Mazrou et al., 2024), we have demonstrated a prograding delta in an intertidal zone, on the basis of fieldwork yielding new sedimentological and palaeontological descriptions and interpretations. These are completely contrary to those of previous authors, who proposed rivers, lakes, sabkha, etc., as we shall demonstrate in the present note. However, in their comment, Dahoumane et al. (2025, in this issue) have accused us, without any valid argument, of having borrowed the work of other authors without citing them, claiming everything presented in our paper to be erroneous, and not based on work by Dahoumane herself or Dahoumane et al., but on so-called references cited. We shall provide proof in the present paper that not a single line has been borrowed from anyone, and also demonstrate that Dahoumane and Dahoumane et al. are not familiar with the basics of sedimentology, which makes them poor judges of sedimentary geology in any objective way. In addition, they do not know the Triassic terrains of Zarzaitine, confuse Triassic formations with those of Jurassic age that outcrop in the study region, and cite false bibliographic references to support their ‘claims’. We shall illustrate below that no information, detail or anything else was presented by Dahoumane et al. concerning the Triassic terrain studied, except for a plate presenting photographs, interpretations of which are all erroneous. We would have appreciated academic critique that could have helped us improve our work, instead of wasting our time responding to false allegations and nonsensical comments.